Bioequivalence assessment of topical clobetasol propionate products using visual and chromametric assessment of skin blanching - Wai Ling Au; Michael Skinner; Isadore Kanfer (Frontiers Media S.A., 2008)
ABSTRACT - PURPOSE: The assessment of the degree of skin blanching following the application of a formulation containing a topical corticosteroid has been established as a surrogate method for the determination of bioequivalence of such topical preparations. Whereas initially the procedure involved visual assessment of the blanching response, an instrumental procedure using a chromameter was subsequently recommended as the method of choice in such evaluations. In this study, both visual and chromametric assessments have been carried out on two topical creams containing clobetasol propionate (0.05%) and the results from both methods are compared and discussed. METHODS: Human subjects (volunteers) were subjected to screening using a cream containing 0.05% clobetasol propionate, in order to identify appropriate subjects for inclusion in the study. Subsequently the study was implemented according to the FDA guidance using both visual and chromameter assessment techniques. Blanching responses were assessed visually by three trained, independent observers and instrumentally using a Chromameter. An ED50 of 36 min was used as the dose duration based upon data previously obtained from a pilot study using the same topical corticosteroid reference product. A visual rating scale of 0-4 and the a-scale readings from the chromameter were used. RESULTS: The visual and chromameter blanching profiles showed similar blanching responses and corresponded well with each other. The 90% confidence interval for the visual and chromameter data were calculated using Lock's method and when only the data obtained from 23 subjects who were identified as "detectors" (according to the FDA guidance) were used, the products fell within the bioequivalence acceptance range of 80-125% using the visual assessment method (99.3-111.6%) whereas the data using a chromameter (86.5-129.3%) were just outside the acceptance limits. However, when all subjects (n=34) were included in the calculations, both the visual (97.9-109.2) and chromameter (90.2-120.7) data fell within the acceptance range for the declaration of bioequivalence.CONCLUSIONS: Whereas visual data indicated bioequivalence using either data from "detectors" or data from all subjects, the chromameter data from "detectors" only indicated bioinequivalence but inclusion of all subject data fell within the acceptance range to be declared bioequivalent.